Hubungan Pengetahuan Perawat Tentang Vaksin COVID-19 dengan Kecemasan Menghadapi Vaksinasi COVID-19 - Wan Nishfa Dewi; Sri Fitri Yanti; Gamya Tri Utami (STIKes Payung Negeri Pekanbaru, 2022)
Abstract Apparently, during the COVID-19 pandemic, nurses became the front-line health care professionals who were required to readiness physically immune. Nurses' immunity can be achieved using COVID-19 vaccination. However, not all nurses have a better understanding of COVID-19 vaccination which may cause their decision to be vaccinated. This study aims to determine the relationship between nurses' knowledge about the COVID-19 vaccine and nurses' anxiety about the COVID-19 vaccination. This study used a quantitative analytic approach with a cross-sectional design. The sample of this study was 80 respondents which were selected using a simple random sampling technique. A questionnaire used for this study has been tested for its validity and reliability. Data collection was analysed using univariate and bivariate analysis. The results of this study showed that the majority of respondents had good knowledge of 72 people (90.0%) and appropriate knowledge of 10 (10.0%). Some of the respondents experienced mild anxiety with 72 people (90, 0%). The respondents who have good knowledge of mild anxiety levels are 68 people (94.4%) and respondents who have good knowledge of moderate-severe anxiety are 4 people (56.0%), respondents who are knowledgeable enough about mild anxiety namely as many as 4 people (50.0%) and respondents who have sufficient knowledge with moderate-severe anxiety are 4 people (50.0%). Based on the Chi-Square test, it is known that the p-value = 0.003 (P-value < 0.05). Respondents who have good knowledge will experience mild anxiety. Keywords anxiety, knowledge, nurse, COVID-19 vaccine, vaccination